Українська наука : минуле, сучасне, майбутнє 2012, Випуск 17 - (:unkn) unknown (Економічна думка, 2012)
Збірник наукових праць містить статті, в яких досліджено актуальні проблеми економіки, історії та політології. Для науковців, викладачів, студентів, а також усіх, кого цікавить розвиток науки в Україні. The collection of scientific works contains the articles of scientists, who are engaged in the actual problems of development of economy and management, history and political science. For scientists, teachers, students, and also for everyone who is interested by development of science in Ukraine.
Ukrainian science: the past, modern, future 2012, Edition 17